2011
DOI: 10.1182/blood-2010-02-269514
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib resistance in mantle cell lymphoma is associated with plasmacytic differentiation

Abstract: Bortezomib induces remissions in 30%-50% of patients with relapsed mantle cell lymphoma (MCL). Conversely, more than half of patients' tumors are intrinsically resistant to bortezomib. The molecular mechanism of resistance has not been defined. We generated a model of bortezomibadapted subclones of the MCL cell lines JEKO and HBL2 that were 40-to 80-fold less sensitive to bortezomib than the parental cells. Acquisition of bortezomib resistance was gradual and reversible. Bortezomib-adapted subclones showed inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 57 publications
7
70
2
Order By: Relevance
“…13,14 Leung-Hagesteijn et al 13 recently demonstrated that MM cells achieve bortezomib resistance via de-commitment to terminal plasma cell maturation, others have instead found that this resistance could be related to plasmacytic differentiation. 15 Nonetheless, the use of NAs during the induction phase followed by auto-SCT has been associated with improvement in the quality of responses, with a higher number of patients achieving VGPR or better, which in turn translates into a major benefit for OS and PFS. 6,12,16,17 Although auto-SCT after NAs induction can result in sustained responses in the majority of cases, still there are some patients relapsing within a year after auto-SCT and this group has poorly been characterized.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Leung-Hagesteijn et al 13 recently demonstrated that MM cells achieve bortezomib resistance via de-commitment to terminal plasma cell maturation, others have instead found that this resistance could be related to plasmacytic differentiation. 15 Nonetheless, the use of NAs during the induction phase followed by auto-SCT has been associated with improvement in the quality of responses, with a higher number of patients achieving VGPR or better, which in turn translates into a major benefit for OS and PFS. 6,12,16,17 Although auto-SCT after NAs induction can result in sustained responses in the majority of cases, still there are some patients relapsing within a year after auto-SCT and this group has poorly been characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmacytic differentiation, driven by IRF4 overexpression, has been linked to bortezomib resistance in MCL [Perez-Galan et al 2011], while MYC is a direct IRF4 target in activated B cells and myeloma [Shaffer et al 2008]. Combining CPI203 with lenalidomide inhibited transcriptional overexpression of IRF4 and MYC and overcame bortezomib resistance in vivo [Moros et al 2014].…”
Section: Lymphomamentioning
confidence: 99%
“…Bortezomib induces apoptosis in MCL through upregulation of the BH3-only protein NOXA (79). NOXA acts as a downstream effector of an integrated cellular stress response triggered by the accumulation of undegraded, polyubiquitinated proteins that induce endoplasmic reticulum stress and the generation of reactive oxygen species (80). Single-agent bortezomib therapy was shown to induce responses in 30%-50% of cases, even in patients who failed to respond to prior dose-intensive therapy or who had bulky disease (81).…”
Section: Target Therapy In Mcl: a Promise Of More Successful Treatmentsmentioning
confidence: 99%